Children's metabolic expenditure during object projection skill performance: New insight for activity intensity relativity. Issue 15 (3rd August 2019) - Sacko, Ryan S.; Nesbitt, Danielle; McIver, Kerry; Brian, Ali; Bardid, Farid; Stodden, David F.
ABSTRACT: Objective : To examine children's energy expenditure (EE) during object projection skill performance at three intensity intervals.Methods : Children's (42, Mage = 8.1) average metabolic equivalents of task (METs) were calculated using a COSMED K4b2 while they repeatedly performed blocks of kicking, throwing (overhand), and striking (two-handed) during 6, 12, and 30-s interval conditions. A repeated-measures analysis of covariance examined differences in METs while controlling for skill level.Results : Data indicated a main effect for interval condition ( df = 2, 123, F = 94.36, p <.001, η 2 = .605). Post hoc t -tests demonstrated decreasing performance interval times yielded progressively higher METs ( p <.001) across the three conditions (30s = 4.5±0.8 METs, 12s = 6.3±1.3, 6s = 8.3±1.6). There also was a main effect for sex ( df = 1, 120, F = 52.28, p <.001 η 2 = .305). Boys demonstrated higher METs at each performance interval ( p <.001).Conclusion : Skill practice with a maximum of one trial every 30s resulted in the equivalent of at least moderate physical activity (>4.0 METs) and intervals of 6s demonstrated vigorous physical activity (>7.0 METs). Practicing/performing object projection skills, even at intervals that allow for adequate instruction and feedback (i.e., 1 trial/30s), promotes MVPA in children.